Academic functioning of youth in foster care: The influence of unique sources of social support. (February 2021) - McGuire, Austen; Gabrielli, Joy; Hambrick, Erin; Abel, Madelaine R.; Guler, Jessy; Jackson, Yo
Highlights: Four social support sources were examined in relation to academic success for youth in foster care. Teacher social support was the only source of support associated with grades and behavioral health. Placement changes was negatively associated with behavioral health functioning. Findings highlight the importance of teacher social support in school for youth in foster care. Abstract: Youth in foster care often experience more difficulty in school compared to their non-foster care peers. Difficulties exist across domains of academic functioning, including both performance (e.g., low grades) and behavioral health (e.g., high externalizing concerns) in school. One factor that has been shown to be associated with positive academic functioning in the general population but remains to be comprehensively examined among youth in foster care is social support. This includes examining specific sources of support for youth in foster care and taking into consideration the context of frequent placement disruptions many children in foster care experience. This study sought to determine which sources of social support are associated with academic functioning for youth in foster care by examining child-report of social support from parents, teachers, friends, and classmates in relation to school grades and teacher-reported behavioral health outcomes. Information on each source of social support was obtained from the self-report of 257 youth in foster care, and information on placement characteristics were obtained from child welfare casefiles. Teachers provided information on youth's behavioral health in school, and academic grades were obtained from school records. Results suggested that youth reported teacher social support, as compared to parent, friend, or classmate social support, was most influential for both performance and behavioral health in school. Findings highlight the need for additional research on the important role of teachers for promoting academic success amongst youth in foster care, as well as the importance of placement changes in relation to academic functioning.